Analysis of the Impact of Full Day School on the Character Development of Grade V Students of Al-Hidayah Islamic Elementary School Besusu - Farastiti Salsabila Amrin; Yusdin Gagaramusu; Khairunnisa Khairunnisa; Zulnuraini Zulnuraini; Ammar Abdullah Joni Guci (Papanda Publisher, 2026)
This study aims to analyze the impact of the Full Day School policy on the development of religious character among fifth-grade students at SD Islam Al-Hidayah Besusu. The implementation of Full Day School, which operates from 07.00 to 15.00, provides extended learning time that integrates academic activities with routine religious practices, including dhuha prayer, zuhur prayer in congregation, daily supplications, and Qur’an recitation. This qualitative descriptive research involved the principal, classroom teachers, parents, and seven fifth-grade students as informants. Data were collected through observation, in-depth interviews, and documentation, and analyzed using Miles and Huberman’s model consisting of data reduction, data display, and conclusion drawing. The findings reveal that Full Day School contributes positively to students’ religious character development. Students show increased discipline in performing worship, politeness, honesty, responsibility, and empathy toward peers. Daily routines and teacher modeling play a significant role in strengthening these values. Social activities such as class duties, teamwork, and maintaining cleanliness further enhance students’ sense of responsibility and cooperation. Although some challenges emerge, such as student fatigue due to long school hours, these do not diminish the overall positive impact when balanced with engaging learning methods and parental support at home. In conclusion, the Full Day School system effectively fosters religious character formation through structured routines, prolonged interaction with teachers, and consistent religious habituation, making it a strategic approach to strengthening student character in elementary education.